Repair method for improving tap density of recycled graphite

By soaking, pickling, calcining and spherical treatment of the recovered graphite powder, the problem of low tap density of recycling graphite is solved, and the high tap density and battery performance are improved.

CN120553697APending Publication Date: 2025-08-29WUHAN RIKOMAY NEW ENERGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510556118.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-29
Publication Date
2025-08-29

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the tap density of recovered graphite, resulting in limited application in batteries.

Method used

Impurities are removed by soaking the initial recovery graphite powder, pickling, calcining, etc., and then mixed with the coating to form a viscous substance, forming microspheres and calcining at high temperatures, and finally spherical treatment is carried out to improve the morphology and particle size.

Benefits of technology

The tap density of the recovered graphite was significantly improved, from 0.8g/cm3 to 1.22g/cm3, and the morphology was more regular, improving the energy density and circulation performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120553697A_ABST
    Figure CN120553697A_ABST
Patent Text Reader

Abstract

The invention relates to a repairing method for improving the tap density of recycled graphite, which comprises the following steps: stripping a graphite negative plate obtained by disassembling a waste retired lithium ion battery cell to obtain initially recycled graphite powder; sequentially carrying out organic solvent soaking washing, acid pickling and calcination on the initially recycled graphite powder to remove residual electrolyte by-products, metal impurities and a binder; mixing the impurity-removed graphite powder with a coating at a high speed, and mixing with a small amount of solvent to form a viscous state; shaping the viscous mixture to obtain graphite microspheres, and slightly drying to control moisture; calcining the microsphere graphite at high temperature; crushing the calcined microspherical graphite to control the particle size of the material; and spheroidizing the microsphere graphite with qualified particle size. The method has the beneficial effects that the morphology and initial particles of the recycled graphite can be remodeled, the tap density of the recycled graphite is improved, and the tap density of the recycled graphite powder is improved from 0.8 g / cm < 3 > to about 1.22 g / cm < 3 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of resource recycling and inorganic material repair, and in particular to a repair method for improving the tap density of recycled graphite. Background Art

[0002] With the retirement and scrapping of a large number of lithium batteries, more and more research on the recycling and utilization of lithium battery resources is being carried out in major institutions. In particular, high-value waste positive electrode materials are favored by everyone, while research on lower-value waste graphite mainly focuses on the stripping of graphite powder and copper foil, how to purify copper foil, how to purify graphite powder, how to increase the gram capacity of graphite powder, etc. However, few people have studied the processing performance application of recycled graphite powder in battery cells, such as the tap density and compaction density of graphite and the expansion rate during the subsequent charging and discharging process.

[0003] Tap density is relatively important for the application of graphite. Tap density is one of the key indicators to measure the performance of graphite negative electrode. It indicates the mass of graphite negative electrode material per unit volume. High tap density means that more negative electrode material can be filled in the same volume, thereby improving the energy density and endurance of the battery. In addition, tap density is interrelated with other technical indicators such as specific surface area, particle size distribution, compaction density, etc., which jointly determine the overall performance of the graphite negative electrode. Appropriate particle size distribution can increase tap density, thereby improving the energy density of the battery, while reasonable compaction density helps to maintain the cycle performance and life of the battery.

[0004] However, after the recycled graphite is peeled off, the primary particles are destroyed and contain various metal impurities and organic impurities, resulting in the tap density of the recycled graphite being only 0.8g / cm 3 , which is far from meeting the requirements for application in battery cell manufacturing process.

[0005] Patent CN101710632B discloses a method for recycling and repairing waste graphite, anode material for lithium-ion batteries. The method regenerates and repairs waste graphite by treating the graphite with an acetone solution coated with cellulose acetate and then calcining it to increase the gram capacity of the recycled graphite to 335.7 mAh / g and a tap density of only 1.07 g / cm 3 , but the subsequent material application stage is not involved.

[0006] Patent CN105600778B discloses an automated device for increasing the tap density of spherical graphite. The device performs spheroidization treatment on newly produced graphite, but it is difficult to treat recycled graphite with special morphology, and the improvement of the tap density of the recycled graphite is limited. Summary of the Invention

[0007] The technical problem to be solved by the present invention is to provide a repair method for improving the tap density of recycled graphite, so as to solve the deficiencies in the prior art.

[0008] The technical solution of the present invention to solve the above technical problems is as follows:

[0009] A repair method for improving the tap density of recycled graphite comprises the following steps:

[0010] S1. Peeling off the graphite negative electrode sheets obtained by disassembling waste and retired lithium-ion batteries to obtain initial recycled graphite powder;

[0011] S2, sequentially performing organic solvent soaking washing, acid washing, and calcination on the initially recovered graphite powder to remove residual electrolyte byproducts, metal impurities, and binder;

[0012] S3, mixing the graphite powder after impurity removal with the coating at a high speed, and mixing with a small amount of solvent to form a viscous state;

[0013] S4. shaping the viscous mixture to obtain graphite microspheres, and slightly drying to control the moisture content to ensure that the graphite microspheres can flow normally;

[0014] S5. calcining the microspherical graphite at a high temperature to achieve modification and coating of the microspherical graphite through calcination, thereby ensuring that the morphology of the graphite is more regular;

[0015] S6. crushing the calcined microspherical graphite to control the particle size of the material;

[0016] S7. The graphite with qualified particle size is spheroidized. Through the shaping of the spheroidizing equipment, a small amount of fine powder is removed and the material morphology is made more round, thereby forming recycled graphite with high tap density.

[0017] On the basis of the above technical solution, the present invention can also be improved as follows.

[0018] Furthermore, the powder stripping method of the graphite negative electrode sheet includes one or more combinations of mechanical crushing and screening, coarse crushing, calcining and screening, and solvent treatment for powder removal.

[0019] Furthermore, the organic solvent immersion washing in S2 is specifically as follows:

[0020] The initial recovered graphite powder is washed with an organic solvent at a solid-liquid ratio of 1:2 to 6, the washing time is 5 minutes to 50 minutes, the washing temperature is 30°C to 50°C, the washing method is one of ultrasound and stirring or a mixture of the two, and after washing, the graphite product is filtered through a plate and frame filter to obtain a graphite product with residual electrolyte by-products removed, and the organic solvent is a mixture of one or more of dimethyl carbonate, ethanol, nitrogen-methyl pyrrolidone, dimethyl sulfoxide, and nitrogen-nitrogen dimethylformamide.

[0021] Furthermore, the initially recovered graphite powder is washed with an organic solvent at a solid-to-liquid ratio of 1:2, 1:3, 1:4, 1:5, or 1:6.

[0022] Furthermore, the pickling in S2 is specifically as follows:

[0023] The graphite product obtained by the first step of impurity removal is washed with an acid solution at a solid-liquid ratio of 1:2 to 6, the pH of the acid solution is 2 to 5, the washing time is 30 minutes to 120 minutes, the washing temperature is 50°C to 90°C, the washing method is one of ultrasound and stirring or a mixture of the two, and after washing, the graphite product is filtered through a plate and frame filter to obtain a graphite product from which metal impurities are removed. The acid solution is a mixture of water and one or more of nitric acid, sulfuric acid, hydrochloric acid, phosphoric acid, acetic acid, and citric acid.

[0024] Furthermore, the graphite product obtained by the first step of impurity removal is washed with acid solution at a solid-liquid ratio of 1:2, 1:3, 1:4, 1:5, or 1:6.

[0025] Furthermore, the calcination in S2 is specifically as follows:

[0026] In a non-oxidizing gas atmosphere, the graphite product obtained by the second step of impurity removal is calcined at 350°C to 500°C with a holding time of 30min to 240min, and the remaining binder in the graphite product is carbonized to obtain a graphite product with the binder removed. The calcination kiln is one of a roller kiln, a rotary kiln, a push plate kiln, a tunnel kiln, and a box-type atmosphere furnace. The non-oxidizing gas is a mixture of one or more of nitrogen, argon, helium, and carbon dioxide. The temperature of carbonization and decomposition of the binder is 350°C to 500°C. Considering the economy, low temperature is used for carbonization to prepare for the subsequent improvement of the tap density.

[0027] Furthermore, in S3, a high-speed mixer is used to mix the graphite powder after impurities removal with the coating at high speed, the mixing speed is ≥700r / min, the mixing time is 30min~240min, the proportion of the coating to the graphite powder is 0.5%~5%, and the coating is a mixture of one or more of citric acid, starch, asphalt, and tar.

[0028] Furthermore, in S3, a homogenizer is used to mix the mixture with a small amount of solvent, the revolution speed is 5r / min~20r / min, the rotation speed is 30r / min~80r / min, the homogenization time is 30min~240min, the proportion of the solvent in the mixture is 5%~20%, and the solvent is a mixture of one or more of water, ethanol, nitrogen-methyl pyrrolidone, dimethyl sulfoxide, and nitrogen-nitrogen dimethylformamide.

[0029] Furthermore, in S4, the viscous mixture is made into graphite microspheres by pressing the viscous mixture into spheres through a mechanical hole device with a fixed size. The pressed spherical graphite composite has no obvious crack defects on the macroscopic surface and has a smooth feature. The hole diameter is 0.5 cm to 3 cm. During the pressing process, the upper and lower plates of the equipment are heated. The heating method is preferably resistance wire heating, the heating temperature is 100°C to 180°C, and the heating time is greater than 3S.

[0030] Furthermore, S5 is specifically as follows: in a non-oxidizing gas atmosphere, the microspherical graphite is calcined at 800°C to 1200°C at a high temperature, and the holding time is 30min to 240min. The non-oxidizing gas is a mixture of one or more of nitrogen, argon, helium, and carbon dioxide. The microspherical graphite is modified and coated by calcination to ensure that the morphology of the graphite is more regular. The kiln for high-temperature calcination can be one of a roller kiln, a rotary kiln, a push plate kiln, a tunnel kiln, and a box-type atmosphere furnace.

[0031] Furthermore, S6 specifically comprises: mechanically crushing the calcined microspherical graphite, and crushing the material through a mechanical mill matched with a classifying wheel to control the particle size of the material.

[0032] Furthermore, the spheroidization equipment used in S7 for spheroidizing the graphite with qualified particle size is one of the honeycomb mill, impact mill, and rod mill equipped with a roller plate with a pretreatment function. At the same time, the coordinated frequency of the induced draft fan is 15Hz to 35Hz to reduce the fine powder content of the highly vibrated graphite finally recovered. The graphite is squeezed, rubbed and collided to crush it, and the graphite with more edges and corners is gradually trimmed into graphite similar to a sphere.

[0033] The beneficial effects of the present invention are:

[0034] 1) Initially recycled graphite powder obtained from various forms of powder stripping processes, especially initial recycled graphite powder with a high content of electrolyte by-products obtained from waste and retired lithium-ion batteries, can also be compatible. Electrolyte-related toxic products can be cleaned in advance through organic solvent washing to avoid the generation of strong carcinogens such as dioxins during subsequent high-temperature calcination;

[0035] 2) The low tap density of the initially recovered graphite powder is only 0.8 g / cm due to the destruction of its primary particles. 3 The process of the present invention can reshape the morphology and initial particles of the recycled graphite and improve the tap density of the recycled graphite. The present invention can increase the tap density of the recycled graphite powder from 0.8 g / cm 3 Increased to 1.22g / cm 3 The tap density is about the same as that of new artificial graphite, providing an engineering process for increasing the tap density of recycled graphite, thereby enhancing the value of recycled graphite and product competitiveness.

[0036] 3) The present invention realizes the morphological change of the recycled graphite through two shaping processes, so that the angular surface morphology becomes approximately spherical and more rounded after the first ball calcination and the second spheroidization roller pressing and crushing treatment, and the tap density is further improved, which is no longer affected by the initial broken particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is the microscopic morphology of the initially recovered graphite powder of Example 2;

[0038] Figure 2 This is a microscopic morphology of the recovered graphite product finally obtained in Example 2;

[0039] Figure 3 This is a diagram showing changes in tap density during the process of Example 1;

[0040] Figure 4 This is a diagram of the fully charged interface of a battery cell made from the materials finally obtained in Comparative Example 1 and Example 2. DETAILED DESCRIPTION

[0041] The principles and features of the present invention are described below with reference to the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0042] Example 1

[0043] A repair method for improving the tap density of recycled graphite comprises the following steps:

[0044] S1. Collecting graphite negative electrode sheets obtained by disassembling waste and retired lithium-ion batteries, then mechanically grinding and pulverizing them, and sieving them through a 200-mesh sieve to obtain initial recycled graphite powder;

[0045] S2. The initially recovered graphite powder was mixed with dimethyl carbonate in a mass solid-liquid ratio of 1:3, and heated to 30° C. The mixture was stirred and ultrasonicated in a container for 20 minutes, and then filtered through a plate and frame filter press to obtain the first step of impurity-removed graphite product, thereby removing electrolyte by-products;

[0046] Then, pickling is performed to remove impurities. Sulfuric acid is used to prepare an acid solution with a pH of 4. The reaction is carried out in a stirred reactor at a solid-liquid ratio of 1:4 between the graphite product and the acid solution. The reaction is heated to 80°C for 120 minutes. The graphite product after the second step of impurity removal is then obtained by plate and frame filter pressing to remove metal impurities.

[0047] The graphite product after acid washing is calcined in a push plate kiln and kept at 380°C for 180 minutes under a nitrogen atmosphere to obtain the graphite product after the third step of impurity removal, in which the binder is removed;

[0048] S3, mixing the graphite powder after impurity removal with citric acid at a high speed of 1200 r / min for 30 min, with the citric acid added in a proportion of 2% of the graphite powder, and then mixing it with 10% by weight of deionized water in a homogenizer to form a viscous state, with an orbital speed of 5 r / min, a rotation speed of 80 r / min, and a homogenization time of 240 min to obtain a viscous mixture;

[0049] S4, shaping and drying the viscous mixture in a ball-making machine, the ball size is 3 cm in diameter, the upper and lower extrusion plate temperatures are 150° C., the pressing time is 5 seconds, and graphite microspheres with smooth surfaces are obtained;

[0050] S5. calcining the graphite microspheres in an argon atmosphere in a roller kiln at a temperature of 1200° C. for 120 min to obtain coated modified graphite microspheres;

[0051] S6. Controlling the particle size of the coated modified graphite microspheres in a jet mill to a particle size of D50 = 14 μm;

[0052] S7. The micro-spherical graphite with qualified particle size is pre-treated by a grinding disc to spheroidize the material, and then the material is subjected to secondary grinding by a rod grinding to obtain recycled graphite with a particle size of D50 = 12 μm. At the same time, the induced draft fan frequency is 25 Hz to remove tiny fine powder, and finally a recycled graphite product with high tap density is obtained.

[0053] Example 2

[0054] A repair method for improving the tap density of recycled graphite comprises the following steps:

[0055] S1. Collecting graphite negative electrode sheets obtained by disassembling waste and retired lithium-ion batteries, and then washing and removing powder. Treating the graphite negative electrode sheets with an 80°C aqueous solution, peeling off the graphite powder from the copper foil, and then drying to obtain initial recovered graphite powder;

[0056] S2. The initially recovered graphite powder was mixed with ethanol at a mass solid-liquid ratio of 1:4, and heated to 30° C. The mixture was stirred and ultrasonicated in a container for 30 minutes, and then filtered through a plate and frame filter press to obtain the first step of impurity-removed graphite product, thereby removing electrolyte by-products;

[0057] Then, pickling is performed to remove impurities. Sulfuric acid is used to prepare an acid solution with a pH of 5. The reaction is carried out in a stirred reactor at a solid-liquid ratio of 1:5 between the graphite product and the acid solution. The reaction is heated to 90°C for 100 minutes. The graphite product after the second step of impurity removal is then obtained by plate and frame filter pressing to remove metal impurities.

[0058] The acid-washed graphite product is calcined in a rotary kiln and kept at 450°C for 120 minutes under a nitrogen atmosphere to obtain the recycled graphite product after the third step of impurity removal, removing the binder;

[0059] S3, the graphite powder after impurity removal was mixed with starch at a high speed of 1000 r / min for 30 min, the starch addition ratio was 4% of the graphite powder, and then mixed with 20% by weight of deionized water in a homogenizer to form a viscous state, the revolution speed was 10 r / min, the rotation speed was 80 r / min, and the homogenization time was 210 min to obtain a viscous mixture;

[0060] S4, shaping and drying the viscous mixture in a ball-making machine, the ball size is 3 cm in diameter, the upper and lower extrusion plate temperatures are 180° C., the pressing time is 10 s, and graphite microspheres with smooth surfaces are obtained;

[0061] S5. calcining the graphite microspheres in a box-type atmosphere furnace under vacuum atmosphere at a temperature of 1000° C. for a holding time of 120 min to obtain coated modified graphite microspheres;

[0062] S6. Controlling the particle size of the coated modified graphite microspheres in a jet mill to a particle size of D50 = 14 μm;

[0063] S7. The micro-spherical graphite with qualified particle size is pre-treated by a grinding disc to spheroidize the material, and then the material is subjected to secondary grinding by a rod grinding to obtain recycled graphite with a particle size of D50 = 11.5 μm. At the same time, the induced draft fan frequency is 35 Hz to remove tiny fine powder, and finally a recycled graphite product with high tap density is obtained.

[0064] Example 3

[0065] A repair method for improving the tap density of recycled graphite comprises the following steps:

[0066] S1. Collecting graphite negative electrode sheets obtained by disassembling waste and retired lithium-ion batteries, and then washing and removing powder. Treating the graphite negative electrode sheets with an 80°C aqueous solution to peel off the graphite powder from the copper foil, and then drying to obtain initial recovered graphite powder;

[0067] S2. The initially recovered graphite powder was mixed with nitrogen-methyl pyrrolidone at a mass solid-liquid ratio of 1:4, and heated to 50° C., stirred and ultrasonicated in a container for 50 minutes, and then filtered through a plate and frame filter press to obtain the first step of impurity-removed graphite product, thereby removing electrolyte by-products;

[0068] Then, pickling is performed to remove impurities. Sulfuric acid is used to prepare an acid solution with a pH of 4. The reaction is carried out in a stirred reactor at a solid-liquid ratio of 1:6 between the graphite product and the acid solution. The reaction is heated to 90°C for 100 minutes. The graphite product after the second step of impurity removal is then obtained by plate and frame filter pressing to remove metal impurities.

[0069] The acid-washed graphite product is calcined in a rotary kiln and kept at 500°C for 120 minutes under a nitrogen atmosphere to obtain the recycled graphite product after the third step of impurity removal, removing the binder;

[0070] S3, the graphite powder after impurity removal was mixed with starch at a high speed of 800 r / min for 60 min, the starch addition ratio was 4% of the graphite powder, and then mixed with 18% by weight of deionized water in a homogenizer to form a viscous state, the revolution speed was 15 r / min, the rotation speed was 60 r / min, and the homogenization time was 180 min to obtain a viscous mixture;

[0071] S4, shaping and drying the viscous mixture in a ball-making machine, the ball size is 2 cm in diameter, the upper and lower extrusion plate temperatures are 180° C., the pressing time is 15 seconds, and graphite microspheres with smooth surfaces are obtained;

[0072] S5. calcining the graphite microspheres in a box-type atmosphere furnace under vacuum atmosphere at a temperature of 1200° C. for 90 min to obtain coated modified graphite microspheres;

[0073] S6. Controlling the particle size of the coated modified graphite microspheres in a jet mill to a particle size of D50 = 14 μm;

[0074] S7. The micro-spherical graphite with qualified particle size is pre-treated by a grinding disc to spheroidize the material, and then the material is subjected to secondary grinding by a rod grinding to obtain recycled graphite with a particle size of D50 = 12.2 μm. At the same time, the induced draft fan frequency is 35 Hz to remove tiny fine powder, and finally a recycled graphite product with a high tap density is obtained.

[0075] Comparative Example 1

[0076] First, the graphite negative electrode sheets obtained by disassembling the waste and retired lithium-ion batteries are collected, and then washed to remove the powder. The graphite negative electrode sheets are treated with an 80°C aqueous solution, and the graphite powder is peeled off from the copper foil, and then dried to obtain the initial recovered graphite powder.

[0077] The initial recovered graphite powder was mixed with starch at a high speed of 1000 r / min for 30 min, and the starch addition ratio was 4% of the graphite powder;

[0078] The mixture of starch and graphite powder was calcined in a roller kiln under a nitrogen atmosphere at a temperature of 450°C and a holding time of 2 hours to finally obtain coated modified graphite powder.

[0079] Figure 1 This is a microscopic morphology of the initially recovered graphite powder in Example 2. Since it has just been peeled off from the copper foil, the morphology of the original graphite particles has been destroyed, becoming angular and disorderly;

[0080] Figure 2 This is a microscopic morphology of the recycled graphite product finally obtained in Example 2. It can be seen from the figure that it has become significantly more rounded and presents a spherical structure, which is beneficial to the improvement of the tap density of the material.

[0081] Figure 3 The tap density change diagram of Example 1 shows that the tap density of the recovered graphite increases with the processing of impurity removal, shaping, carbonization, and spheroidization. The tap density of Example 1 finally reaches 1.22 g / cm 3 For Example 2, the final tap density is 1.2 g / cm 3 For Example 3, the final tap density is 1.2 g / cm 3 .

[0082] Figure 4 It is a full charge interface diagram of the whole battery, and the left picture is a full charge interface diagram of the battery cell made of the material of Comparative Example 1. The impurities in Comparative Example 1 were not removed, the tap density was low, and a side reaction occurred when the lithium ions were separated from the positive electrode and embedded in the negative electrode, resulting in lithium ion deficiency, and the failure to embed in all interfaces to form golden Li6C. The right picture is a full charge interface diagram of the battery cell made of the material of Example 2. Due to the good processing performance and almost no impurities, the full charge interface is golden as a whole and the interface is smooth, indicating that the expansion rebound is low when the negative electrode is fully charged, which is conducive to a longer cycle life and calendar life in the later stage.

[0083] The embodiments of the present invention are illustrative and cannot be construed as limiting the present invention. A person skilled in the art can change, modify, replace, and modify the embodiments within the scope of the present invention.

Claims

1. A repair method for improving the tap density of recycled graphite, characterized in that: The steps include: S1. Peeling off the graphite negative electrode sheets obtained by disassembling waste and retired lithium-ion batteries to obtain initial recycled graphite powder; S2, sequentially performing organic solvent soaking washing, acid washing, and calcination on the initially recovered graphite powder to remove residual electrolyte byproducts, metal impurities, and binder; S3, mixing the graphite powder after impurity removal with the coating at a high speed, and mixing with a small amount of solvent to form a viscous state; S4, shaping the viscous mixture to obtain graphite microspheres, and slightly drying it to control the moisture content; S5. calcining the microspherical graphite at high temperature; S6. crushing the calcined microspherical graphite to control the particle size of the material; S7. Spheroidizing the micro-spherical graphite with qualified particle size.

2. A repair method for improving the tap density of recycled graphite according to claim 1, characterized in that: The powder stripping method of the graphite negative electrode sheet includes one or more combinations of mechanical crushing and screening, coarse crushing, calcining and screening, and solvent treatment for powder removal.

3. A repair method for improving the tap density of recycled graphite according to claim 1, characterized in that: The organic solvent immersion washing in S2 is specifically as follows: The initial recovered graphite powder is washed with an organic solvent at a solid-liquid ratio of 1:2 to 6, the washing time is 5 minutes to 50 minutes, the washing temperature is 30°C to 50°C, the washing method is one of ultrasound and stirring or a mixture of the two, and after washing, the graphite product is filtered through a plate and frame filter to obtain a graphite product with residual electrolyte by-products removed, and the organic solvent is a mixture of one or more of dimethyl carbonate, ethanol, nitrogen-methyl pyrrolidone, dimethyl sulfoxide, and nitrogen-nitrogen dimethylformamide.

4. A repair method for improving the tap density of recycled graphite according to claim 1, 2 or 3, characterized in that: The specific pickling in S2 is: The graphite product obtained by the first step of impurity removal is washed with an acid solution at a solid-liquid ratio of 1:2 to 6, the pH of the acid solution is 2 to 5, the washing time is 30 minutes to 120 minutes, the washing temperature is 50°C to 90°C, the washing method is one of ultrasound and stirring or a mixture of the two, and after washing, the graphite product is filtered through a plate and frame filter to obtain a graphite product from which metal impurities are removed. The acid solution is a mixture of water and one or more of nitric acid, sulfuric acid, hydrochloric acid, phosphoric acid, acetic acid, and citric acid.

5. A repair method for improving the tap density of recycled graphite according to claim 1, 2, 3 or 4, characterized in that: The calcination in S2 is specifically as follows: The graphite product obtained by the second step of impurity removal is calcined at 350° C. to 500° C. in a non-oxidizing gas atmosphere for 30 to 240 minutes to carbonize the remaining binder in the graphite product to obtain a graphite product from which the binder has been removed. The calcination kiln is one of a roller kiln, a rotary kiln, a push plate kiln, a tunnel kiln, and a box-type atmosphere furnace. The non-oxidizing gas is a mixture of one or more of nitrogen, argon, helium, and carbon dioxide.

6. A repair method for improving the tap density of recycled graphite according to claim 1, characterized in that: In S3, a high-speed mixer is used to mix the graphite powder after impurities removal with the coating at high speed. The mixing speed is ≥700r / min, the mixing time is 30min~240min, the proportion of the coating to the graphite powder is 0.5%~5%, and the coating is a mixture of one or more of citric acid, starch, asphalt, and tar.

7. A repair method for improving the tap density of recycled graphite according to claim 6, characterized in that: In S3, a homogenizer is used to mix the mixture with a small amount of solvent. The revolution speed is 5r / min to 20r / min, the rotation speed is 30r / min to 80r / min, the homogenization time is 30min to 240min, the proportion of the solvent in the mixture is 5% to 20%, and the solvent is a mixture of one or more of water, ethanol, nitrogen-methyl pyrrolidone, dimethyl sulfoxide, and nitrogen-nitrogen dimethylformamide.

8. A repair method for improving the tap density of recycled graphite according to claim 1, characterized in that: In S4, the viscous mixture is made into graphite microspheres by pressing the viscous mixture into spheres through a mechanical hole device with a fixed size, and the hole diameter is 0.5 cm to 3 cm. During the pressing process, the upper and lower plates of the device are heated at a heating temperature of 100° C. to 180° C., and the heating time is greater than 3 seconds.

9. A repair method for improving the tap density of recycled graphite according to claim 1, characterized in that: S5 specifically comprises: calcining the microspherical graphite at 800° C. to 1200° C. in a non-oxidizing gas atmosphere for 30 min to 240 min, wherein the non-oxidizing gas is a mixture of one or more gases selected from nitrogen, argon, helium, and carbon dioxide.

10. The repair method for improving the tap density of recycled graphite according to claim 1, characterized in that: The spheroidization equipment used in S7 for spheroidizing graphite with qualified particle size is a honeycomb mill, impact mill, or rod mill equipped with a roller plate with pretreatment function. At the same time, the induced draft fan has a coordinated frequency of 15Hz to 35Hz to reduce the fine powder content of the highly compacted graphite finally recovered.

Citation Information

Patent Citations

  • Method for recovering and restoring anode material graphite of waste lithium ion battery

    CN101710632B

  • An automatic equipment for increasing the tap density of spherical graphite

    CN105600778B